Teachers and Students Relation from Ibnu Sina’s Multilevel Reasoning and Neuroscience Perspective: Implications for Islamic Education Development - Mohammad Jailani; Suyadi Suyadi; Kusmana Kusmana (JURNAL INDO-ISLAMIKA, 2021)
Currently, teachers' and students' relations were not ideally treated because of the rapid growth of information technology. The teacher's role was needed in improving students' cognitive, affective and psychomotor skills for facing the recent era. This study was aimed to analyze the teachers and students relation in appropriate models using Ibn Sina's multilevel reasoning and neuroscience perspective. The data were obtained through observing manual and digital scientific journals and research references focusing on this issue. This research was a literature study using a qualitative method. Findings proved that Ibn Sina's multilevel reasoning approach was relevant for improving the student's brain, emotional intelligence, and empathy to their teachers. Teachers should be creative to approach the pupils by providing appropriate advice and character education. Thus this research was expected to contribute to the Islamic education development in this millennial era.